In-vitro Analysis of Different Trichoderma spp. Against Fusarium Rhizome Rot of Ginger (Zingiber officinale Roscoe) - Madan Ghimire; Nirmal Adhikari (AgroEnvironmental Sustainability, 2023)
This study evaluated the effectiveness of four isolates of Trichoderma spp. obtained from various plant protection divisions and commercial products for the biocontrol of Fusarium rhizome rot of ginger (Zingiber officinale Roscoe). Experiments were designed in a completely randomized design (CRD) with five treatments and ten replications. The National Agriculture Research Council (NARC) isolates of Trichoderma spp. were multiplied through direct inoculation on PDA media. Meanwhile, the commercial products of T. harzianum (TRICHO-HR) and T. viride (Biocide Trivi) were prepared as spore suspension. The dual culture technique was used to evaluate the interaction between Trichoderma spp. and Fusarium pathogen. The radial diameter of both Trichoderma and Fusarium was measured every 24 h for 7 days. The experiments in dual cultures demonstrated that various Trichoderma isolates and commercial products significantly inhibited Fusarium mycelial growth. Among the isolates tested, T1-NARC showed the highest efficacy at 57.91% growth inhibition, followed by T2-RPPL (52.50%) and T4-Biocide Trivi (40.98%). However, T3-TRICHO HR displayed lower performance with an inhibition rate of 24.75%. These findings offer valuable insights for the use of Trichoderma spp. as biocontrol agents in ginger cultivation, contributing to improved disease control and enhanced crop health. The observed differences in performance could be attributed to the genetic variations among the isolates.